461 Hypoglossal Nerve Stimulation: Effectiveness of Therapy for Treatment of Positional Obstructive Sleep Apnea. (3rd May 2021) - White, Michelle; Stuewe, Elena; Zacharias, Rajesh; Grover, Aarti; Wein, Richard
Abstract: Introduction: Hypoglossal nerve stimulation (HGNS) therapy is highly effective treatment for patients with moderate-severe obstructive sleep apnea (OSA). Positional OSA is considered when the apnea-hypopnea index (AHI) is at least twice as high in supine position compared with non-supine position. There are few studies in the literature investigating response to HGNS in patients with positional OSA. Methods: Pre- and post-implant polysomnography (PSG) data was retrospectively reviewed in 46 patients who underwent HGNS at a large tertiary care center from November 2017 to March 2020. Supine and non-supine AHI were used to diagnose positional OSA on pre- and post-implant PSG. Pre-implant AHI was recorded from both in-lab PSG as well as home sleep tests, while post-implant AHI was based on in-lab hypoglossal nerve stimulator titration performed three months after device activation. Overall AHI pre- and post-implantation and absolute AHI reduction (pre-implant AHI – post-implant AHI) were evaluated. Basic demographic information including age, sex and BMI were also recorded. Results: 25/46 patients (54%) were diagnosed with positional OSA on pre-implant PSG. Patients with positional OSA had lower pre-implant overall AHI than patients without positional OSA (AHI 29.6 and 38.9, respectively, p<0.05) and lower absolute AHI reduction than patients without positional OSA (18.2 and 26.7, respectively, p<0.05). There were no statistically significant differences in BMI and post-implant overall AHI between these groups. 19/25 patients (76%) with pre-implant positional OSA had persistent positional OSA on post-implant PSG. Conclusion: Patients with positional OSA prior to HGNS had lower pre-implant overall AHI and absolute AHI reduction than patients without positional OSA. However, post-implant overall AHI was comparable, suggesting similar benefit in HGNS therapy regardless of positional OSA diagnosis. HGNS does not appear to resolve positional OSA, given that 76% of patients with positional OSA pre-implantation had persistent positional OSA post-implantation. Positional OSA after HGNS should be recognized in patients with persistent symptoms or inability to tolerate higher device amplitudes, and treatment with combination therapy with positional device can be considered. Support (if any):